Aprendizaje cooperativo como estrategia pedagógica para fortalecer el pensamiento métrico y sistema de medidas en el área de mecánica industrial (2019)
Metric thinking and measurement are important aspects in the teaching of mathematics and related areas, due to its practicality in everyday life. It refers to the general understanding that a person has about magnitude, quantity and the flexible use of the metric systems that are required in different situations. In the field of Industrial Mechanics, it becomes more evident, because its approach fosters a more inclusive education (articulating theory and practice). With this foundation, a study has been initiated, at the Blas Torres de la Torre Industrial Technical Educational Institution, through cooperative learning to boost industrial technical training, from 5 °, during their school training process, so that students find more sense to discover their complementarity, and get motivated to the appropriation of the learning process, allowing to understand its importance and usefulness that it has in today's society.